Ethics and social responsibility practices among entrepreneurs - Mhd. Sarif, Suhaimi (2010)
Ethics and social responsibility are very important values in entrepreneurship ventures. This is particularly essential in decision making process. Ethical conscience reminds entrepreneurs to make trustworthy and profitable entrepreneurship decisions. Likewise, the social responsibility component sought entrepreneurs to make entrepreneurial decisions that can enhance benefits and repelling harms to the stakeholders. This paper investigates the perceptions of entrepreneurs that operated in Klang Valley regarding the practice of ethics and social responsibility among entrepreneurs. The study used personal interview technique with open ended interview questions to obtain the views of 20 entrepreneurs. The findings showed that one thirds of the entrepreneurs perceived that the practice of ethics and social responsibility is almost impossible due to the strong influence of external factors. Nevertheless, these entrepreneurs believed that these values are important. The remaining entrepreneurs viewed that ethics and social responsibility could be possibly practiced despite the strong external factors provided that entrepreneurs have strong belief. Nevertheless, the results of the study were not conclusive considering limitations on small number of interviewees and the location of the business owners. The study proposed that future research to use personal interview and self administered survey with more small business owners from other major cities.